miR-301a-mediated crosstalk between the Hedgehog and HIPPO/YAP signaling pathways promotes pancreatic cancer - Bing Qi; Yuqiong Wang; Xian Zhu; Yanfang Gong; Jing Jin; Hongyu Wu; Xiaohua Man; Feng Liu; Wenzhu Yao; Jun Gao (Cancer Biology & Therapy)
Pancreatic ductal adenocarcinoma (PDAC) poses a significant challenge in oncology due to its dismal prognosis and limited therapeutic options. In this study, we investigated the role of miR-301a in facilitating crosstalk between the Hedgehog (Hh) and HIPPO/YAP signaling pathways during the progression of PDAC. Our findings revealed that miR-301a served as a central regulatory node, targeting Gli1 within the Hh pathway and STK4 within the HIPPO/YAP pathway. Immunohistochemical and molecular analyses confirmed dysregulation of pathway components in pancreatic cancer, underscoring the pivotal role of miR-301a. Functional assays demonstrated the impact of miR-301a on cell proliferation and apoptosis, particularly in synergy with TNF-α. Overall, our study elucidated the intricate interplay between the Hh and HIPPO/YAP pathways mediated by miR-301a, providing valuable insights into potential therapeutic strategies for intervening in PDAC.